2014
DOI: 10.1371/journal.pone.0101370
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Callus Healing for Optimization of Fracture Fixation Stiffness

Abstract: The stiffness of fracture fixation devices together with musculoskeletal loading defines the mechanical environment within a long bone fracture, and can be quantified by the interfragmentary movement. In vivo results suggested that this can have acceleratory or inhibitory influences, depending on direction and magnitude of motion, indicating that some complications in fracture treatment could be avoided by optimizing the fixation stiffness. However, general statements are difficult to make due to the limited n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 55 publications
(68 reference statements)
4
38
0
Order By: Relevance
“…However, while the IFC data are available no quantitative comparison has be made between simulations and the results, instead visually comparing general trends and histological slices has predominated. In Figure 5 , we see simulation results from (A) Burke and Kelly ( 62 ), (B) Lacroix and Prendergast ( 37 ), and (C) Steiner et al ( 65 ) these all consist of a uniform cortical bone and callus geometry, which is made up of non-uniform finite elements, in the case of Burke and Kelly ( 62 ) and Lacroix and Prendergast ( 37 ) they are two dimensional axisymmetric simulations and in Steiner et al ( 65 ) three dimensional. Figure 5 D is a histological section from an in vivo study by Claes and Heigele ( 4 ); we see the callus is non-uniform and asymmetric.…”
Section: Biological Aspectsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, while the IFC data are available no quantitative comparison has be made between simulations and the results, instead visually comparing general trends and histological slices has predominated. In Figure 5 , we see simulation results from (A) Burke and Kelly ( 62 ), (B) Lacroix and Prendergast ( 37 ), and (C) Steiner et al ( 65 ) these all consist of a uniform cortical bone and callus geometry, which is made up of non-uniform finite elements, in the case of Burke and Kelly ( 62 ) and Lacroix and Prendergast ( 37 ) they are two dimensional axisymmetric simulations and in Steiner et al ( 65 ) three dimensional. Figure 5 D is a histological section from an in vivo study by Claes and Heigele ( 4 ); we see the callus is non-uniform and asymmetric.…”
Section: Biological Aspectsmentioning
confidence: 95%
“…The model was implemented as a three dimensional linear-elastic simulation. While this model can capture the events of bone regeneration, Steiner et al ( 65 ) conducted a parameter study of fixator stiffness, which encompassed values used several in vivo studies and achieved comparable outcomes, it is a linguistic representation of observed phenomenon. Thus it is entirely phenomenological and does not encompass any underlying mechanism in physical or chemical terms.…”
Section: Theories and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that rigid fixation has a deleterious impact on the fracture healing cascade while improved fracture healing occurred when axial micromotion is delivered to the fracture site . While these studies provide valuable insight about the role fracture dynamization and interfragmentary movement of the fracture itself have on the healing process (as compared to static fixation techniques), fewer studies have investigated the direct role of fixation stiffness on in vivo fracture healing in a static environment . Gilbert et al investigated tibial fracture healing over 9 weeks in a canine model and observed no significant differences in failure force, stiffness, or energy to failure as a function of fixator stiffness .…”
mentioning
confidence: 99%
“…[13][14][15] While these studies provide valuable insight about the role fracture dynamization and interfragmentary movement of the fracture itself have on the healing process (as compared to static fixation techniques), fewer studies have investigated the direct role of fixation stiffness on in vivo fracture healing in a static environment. 12,[16][17][18] Gilbert et al investigated tibial fracture healing over 9 weeks in a canine model and observed no significant differences in failure force, stiffness, or energy to failure as a function of fixator stiffness. 16 Conversely, Goodship et al reported an inverse relationship between fracture healing time and fixation stiffness in an ovine model.…”
mentioning
confidence: 99%